Measuring the satisfaction of employees based on the service quality of (ATM) Automated Teller Machine of the directorate of education in Thi Qar province: قياس رضا الموظفين بناء على جودة الخدمة لماكينة الصرف الآلي (ATM) لمديرية التربية والتعليم في محافظة ذي قار-العراق - Mohammed Jaber Farhan (مجلة العلوم الهندسية و تكنولوجيا المعلومات, 2020)
The internet and networks have broadened the electronic financial business specifically the transaction of money. The novel banking industry in Iraq countering many obstacles especially security issues. The aggressive competition among the banks to attracting more customers resulting that the quality of the services became the cornerstone. The private banks try to improve the services for the customer by using Automated Teller Machine (ATM). The purpose of this study is describing the explanatory variables for service quality in the research model and examine the effect of service quality variables on employee satisfaction. Two hypotheses were formed to verify if their effect on service quality or not. using Quantitative approach with survey method to quantifies the responses collected via questionnaire. The questionnaires distributed to employees working in the directorate of education are350 just 302was returned and after the examination only 210 questionnaire was valid. Descriptive statistics, Pearson-correlation and multiple linear regression techniques in SPSS were used to analyze quantitative data collected from the questionnaire. the findings are medium agree of ease of use ATM, moderate disagree for accessibility and moderate disagree of security. Regression model finds the service quality factors affect employee satisfaction and as result H1 hypothesis accepted. finally, Pearson-correlation showed a positive relationship to all independent variable on employee’s satisfaction and mentioned the highest positive correlation was the ease of use variable.